1989
DOI: 10.1136/bmj.299.6710.1253
|View full text |Cite
|
Sign up to set email alerts
|

Negative extrathoracic pressure in treatment of respiratory failure in infants and young children.

Abstract: Objective-To assess the efficacy of a newly developed system for applying continuous or intermittent negative (subatmospheric) extrathoracic pressure in respiratory failure.Design Main outcome measures-Inspired oxygen concentration and carbon dioxide pressure before application of negative extrathoracic pressure and two and 48 hours afterwards; duration of treatment; and final outcome (discharge home or death).Results-While arterial oxygen saturation was maintained at constant values 75 infants showed reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…A negative pressure of -0.6 kPa (-6 cm H,O) was applied using a system developed over the past 5 y to overcome the technical difficulties described previously (8). It consists of a chamber with a Perspex lid on an incubator heater base with five portholes to allow easy access to the patient and the insertion of monitoring leads and treatment lines.…”
Section: Cnepmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative pressure of -0.6 kPa (-6 cm H,O) was applied using a system developed over the past 5 y to overcome the technical difficulties described previously (8). It consists of a chamber with a Perspex lid on an incubator heater base with five portholes to allow easy access to the patient and the insertion of monitoring leads and treatment lines.…”
Section: Cnepmentioning
confidence: 99%
“…A new system for applying negative extrathoracic pressure respiratory support has been designed to overcome many of the previous technical problems such as access to the infant, adequate neck seal, and temperature control (8). Preliminary results from ongoing controlled clinical trials suggest that negative extrathoracic pressure support may have benefits beyond those of conventional therapy in the management of lung disease in neonates and infants.…”
mentioning
confidence: 99%
“…Furthermore, it was suggested that the collar could induce a garrotting effect responsible for the potentially harmful increase in endocranial pressure [61]. More recently, however, after substantial technical improvement [62], NPV has been reintroduced for the treatment of respiratory failure [63,64]. PALMER et al [65], using a new model of tank ventilator ( fig.…”
Section: Paediatric Diseasesmentioning
confidence: 99%
“…SAMUELS and SOUTHALL [62] studied, in an uncontrolled clinical trial, the effects of NPV in 88 infants and young children (aged 1 day to 2 yrs) with respiratory failure principally due to bronchopulmonary dysplasia and neonatal distress syndrome. When NPV was initiated, 59…”
Section: Paediatric Diseasesmentioning
confidence: 99%
See 1 more Smart Citation